Effects of voluntary contraction on the soleus H-reflex of different amplitudes in healthy young adults and in the elderly - Batista-Ferreira, Leandra; Rabelo, Natielle Ferreira; Cruz, Gabriel Menezes da; Costa, Juliana Nunes de Almeida; Elias, Leonardo Abdala; Mezzarane, Rinaldo André (Frontiers in Human Neuroscience, 2022)
A number of H-reflex studies used a steady mild voluntary contraction in an attempt to keep the motoneuron pool excitability relatively constant. However, it is not clear whether the voluntary muscle activation itself represents a confounding factor for the elderly, as a few ongoing mechanisms of reflex modulation might be compromised during the aging process. Further, it is well known that the amount of either inhibition or facilitation from a given conditioning depends on the size of the test H-reflex. This fact justifies the study of the effects of voluntary contraction over a wide range of reflex amplitudes. The present results showed significant reflex facilitation for both groups (p<0.05), regardless of their test reflex amplitudes. This points to the hypothesis that age related differences in spinal cord mechanisms do not significantly affect the reflex modulation during a mild voluntary contraction. Simulations with a computational model of the motoneuron pool driven by stationary descending commands yielded qualitatively similar amount of reflex facilitation as compared to human experiments. It is therefore suggested that a mild voluntary muscle contraction to maintain the general motoneuron pool excitability relatively constant can be used in experiments designed to compare both populations. Finally, in an attempt to elucidate the controversy around changes in the direct motor response (M-wave) during contraction, the maximum M-wave (Mmax) was compared between groups and conditions. It was found that the Mmax significantly increases (p<0.05) during contraction and decreases (p<0.05) with age arguably due to muscle fiber shortening and motoneuron loss, respectively.